أثر التكنولوجيا المالية في تعزيز جودة الخدمات المصرفية من وجهة نظر العملاء : دراسة ميدانية على المصارف التجارية الليبية العاملة ببلدية مصراته - مفتاح الشيخ رحيل, محمد; محمد الطرشي, إيمان (Dirasat in Economics and Business, 2026)
This study aimed to identify the impact of financial technology (Fintech) on the quality of banking services in Libyan commercial banks, as well as to assess the current state of Fintech implementation in these banks. The study population consisted of all Libyan commercial banks across both public and private sectors. Due to the large size of the population, a random sampling method was employed. The researcher adopted a quantitative approach to collect primary data from a sample of 250 respondents using a structured questionnaire, achieving a response rate of 84%. Descriptive statistics including means, standard deviations, and percentages were used to answer the study questions, while multiple regression analysis was applied to test the study hypotheses. The findings revealed a statistically significant impact of Fintech on the quality of banking services. However, the overall level of Fintech adoption in most commercial banks was generally weak, except for a relatively adequate infrastructure that was somewhat prepared to support Fintech applications. The study also indicated a lack of modern technologies such as ATMs and limited reliance on modern services like mobile and email banking. Moreover, customers’ sense of security and trust in banking services was found to be low. The study’s findings are expected to contribute to improving the quality of banking services and to provide valuable insights for banking and financial institutions regarding the importance of Fintech adoption.